Protecting the polar marine environment : law and policy for pollution prevention / edited by Davor Vidas. - Vidas, Davor (Cambridge University Press, 2000)
How can we best protect the polar marine environment against pollution? Leading scholars on environmental law, the law of the sea, and Arctic and Antarctic affairs here examine this important question. To what extent do existing global instruments of environmental protection apply to the Arctic Ocean and the Southern Ocean? Can the arrangements adopted at regional, sub-regional and national levels provide adequate protection? This book examines and compares various levels of regulation in protecting the marine environment of the Arctic and Antarctic, with specific attention to land-based activities, radioactive waste dumping, and shipping in ice-covered waters. Developments since the establishment of the Arctic Council in 1996 and the entry into force of the Protocol on Environmental Protection to the Antarctic Treaty in 1998 are also discussed. This is a volume that will appeal to polar specialists and to all those interested in environmental law and policy.